Pemanfaatan Marketplace dan Digital Marketing Pada Usaha Himpunan Wanita Penyandang Disabilitas Kota Bengkulu - Esti Pasaribu; Yefriza; Retno Agustina Ekaputri; Azansyah (Madani : Indonesian Journal of Civil Society, 2023)
During the pandemic covid-19, there are many people in Bengkulu who are not working anymore, while the housewives should be able to use their free time more productively, including for Himpunan Wanita Difabel Indonesia (HWDI). One of the causes is the lack of knowledge and experience of members in the field of marketing using technology, for example by utilizing the marketplace. For this reason, Bengkulu University carries out community service activities (PKM) in the form of counseling about the marketplace as an effort to increase business competitiveness for HWDI products. With this counseling, HWDI members currently have a smooth business selling their products so that their income increases. In addition to creating a marketplace account, HWDI members also create a QRIS account to make the payment system easier. The activity was carried out on June 11, 2022 at the secretariat of HWDI in Padang Harapan, Gading Cempaka Bengkulu City.